Assessment of photosynthetic performance in the two life history stages of Alaria crassifolia (Laminariales, Phaeophyceae). Issue 1 (25th July 2018) - Borlongan, Iris Ann; Nishihara, Gregory N.; Shimada, Satoshi; Terada, Ryuta
SUMMARY: Understanding of the physiological responses of kelp to environmental parameters is crucial, especially in the context of environmental change that may have contributed to the decline of kelp forests all over the world. The current study presents the photosynthetic characteristics of the macroscopic sporophyte and microscopic gametophyte stages of the brown alga Alaria crassifolia from Hokkaido, Japan, as determined by examining their photosynthetic responses over a range of temperature and irradiance using dissolved oxygen and chlorophyll fluorescence measurements. Net photosynthetic rates of the sporophyte were consistently higher than those of gametophyte across temperature gradients and irradiance levels. Photosynthesis–irradiance curves at 8°C, 16°C, and 20°C revealed similar initial slopes ( α = 0.4–0.9) on the two life history stages, but higher compensation ( E c = 4–7 μmol photons m −2 s −1 ) and saturation irradiances ( E k = 53–103 μmol photons m −2 s −1 ) for the sporophyte than for the gametophyte ( E c = 0–7 μmol photons m −2 s −1 ; E k = 7–10 μmol photons m −2 s −1 ). Both stages exhibited chronic photoinhibition, as shown by the failure of recovery in their maximum quantum yields ( F v /F m ) following high irradiance stress, with greater possibility of photodamage at low temperature. Gametophytes were less sensitive to low temperatures than sporophytes, given their relatively stable F v /F m response. Nevertheless, temperature optima for photosynthesis of both stages coincide with each other at 20–23°C, which correspond to the growth and maturation periods of A. crassifolia in Japan. This species is also likely to suffer from thermal inhibition as both GP rates and F v /F m decreased above 24°C.